Aspects of Synodality in Recent Catechetical Documents: The Directory for Catechesis and Antiquum Ministerium - Sultana, Carl-Mario (Verbum Vitae, 2024)
This article seeks to draw out the implications of synodality as journeying together in some aspects of the Directory for Catechesis (2020) and of Antiquum Ministerium (2021). These notions of synodality cannot be fished out of these documents in an immediate way. The method which will be adopted is a bibliographical one where several texts will be analysed. The first part will seek to give a working definition of synodality. For a balanced view, this will be supplemented by some difficulties in synodality today. This will be followed by a very brief outline of how catechesis changed as a result of the Second Vatican Council. The Directory for Catechesis and Antiquum Ministerium will then be presented in terms of contents within them which point at or call for synodality. Finally, specific aspects of the contents of these two documents will be studied in view of their practical implications to catechesis in the contemporary secularised world, namely synodality within the structures of the Church entrusted with catechesis; accompaniment; listening and speaking, and discernment.